Acute Decompensated Heart Failure Pasca Kardioversi pada Pasien Lansia dengan Diabetes Mellitus dan Chronic Kidney Disease : Sebuah Laporan Kasus - Sugiharto, Firman; Larashati, Defa; Sari, Wulan Puspita; Prawesti, Ayu; Mirwanti, Ristina; Nuraeni, Aan (Universitas Malahayati, 2024)
ABSTRACT Acute decompensated heart failure (ADHF) is one of the spectrum of heart failure (HF). ADHF is defined as a clinical syndrome characterized by worsening HF symptoms, in which decreased cardiac output is the main characteristic leading to inadequate tissue perfusion and systemic venous congestion. ADHF is a strong predictor of readmission and post-hospitalization death, with a mortality rate of 20% after discharge from the hospital. Nurses have an essential role in comprehensive nursing care. A 73-year-old man came to the emergency room with complaints of palpitations without chest pain; the patient denied orthopnea and complained of swelling in both legs. The patient had a history of coronary heart disease (CHD), having been treated in 1998 for cardiac stent installation. The patient was treated in the ICU due to ventricular arrhythmia and hypotension. What is interesting about this case is that apart from the patient experiencing recurrent Ventricular Tachycardia (VT), the patient also had no complaints of shortness of breath, and a Blood Gas Analysis (BGA) examination found the patient to have hyperoxemia and the results of a diagnostic thorax examination showed no pulmonary oedema. Patients receive diuresis, inotropic, anti-arrhythmic and electrolyte fluid therapy. The patient was treated in the ICU for ten days and then moved to the inpatient room. This case report emphasizes the importance of accurate initial assessment of ADHF patients and the role of nurses in intensive care for ADHF patients. Nurses must be able to recognize signs and symptoms of ADHF emergencies early so that the goals of ADHF therapy to increase organ perfusion and limit the increase in severity of heart injury can be carried out quickly and precisely. Treatment of ADHF patients requires appropriate nursing interventions so that the quality of life of patients with HF can be improved. The nurse's role in preparing discharge planning as an essential preventive measure is to reduce the risk of readmission. Keyword: Acute Decompensated Heart Failure, Elderly, Intensive Care Unit, Nursing Care. ABSTRAK Acute decompensated heart failure (ADHF) merupakan salah satu spektrum dari Heart failure (HF). ADHF didefinisikan sebagai sindrom klinis yang ditandai oleh gejala HF yang memburuk, di mana penurunan curah jantung menjadi karakteristik utama yang mengarah pada perfusi jaringan yang tidak adekuat dan kongesti vena sistemik. ADHF merupakan prediktor kuat terjadinya rawat inap kembali dan kematian pasca rawat inap dengan angka kematian sebesar 20% setelah keluar dari rumah sakit. Perawat memiliki peran penting dalam menilai secara komprehensif dalam asuhan keperawatan. Pria berumur 73 tahun datang ke IGD dengan keluhan jantung berdebar tanpa ada nyeri dada, ortopnea disangkal oleh pasien, dan mengeluh bengkak pada kedua kaki. Pasien memiliki riwayat penyakit jantung coroner (CHD), pernah dirawat pada tahun 1998 untuk pemasangan stent jantung. Pasien dirawat di ICU dikarenakan kondisi Ventrikel aritmia dan hipotensi. Hal menarik dari kasus ini, selain pasien mengalami Ventrikel Takikardia (VT) berulang, pasien juga tidak memiliki keluhan sesak nafas dan pemeriksaan Analisa Gas Darah (AGD) ditemukan pasien mengalami hiperoxemia serta hasil pemeriksaan diagnostik thorax foto menunjukan tidak adanya pulmonary edema. Pasien mendapatkan terapi diuresis, inotropik, anti-aritmia dan cairan elektrolit. Pasien dirawat di ICU selama 10 hari lalu pindah ke ruang rawat inap. Pada case report ini menekankan pada pentingnya ketepatan pengkajian awal pasien ADHF dan peran perawat dalam perawatan intensif pasien ADHF. Perawat harus mampu mengenali tanda dan gejala kegawatan ADHF secara dini sehingga tujuan terapi ADHF untuk meningkatkan perfusi organ dan membatasi peningkatan keparahan cedera jantung dapat dilakukan secara cepat dan tepat. Perawatan pasien ADHF memerlukan interevensi keperawatan yang tepat sehingga kualitas hidup pasien dengan HF dapat ditingkatkan. Peran perawat dalam mempersiapkan discharge planning sebagai tindakan preventif penting dilakukan untuk mengurangi resiko readmisi. Kata Kunci: Acute Decompensated Heart Failure, Asuhan Keperawatan, Intensive Care Unit, Lansia.